COVID-19 vaccine acceptance and hesitancy in patients with Parkinson's disease - Zhou, Yifan; Lin, Zhengyu; Wan, Xiaonan; Liu, Jun; Ding, Jianqing; Zhang, ChenCheng; Ren, Kang; Li, Dianyou; Wu, Yiwen (Frontiers in Public Health, 2022)
BACKGROUND: As coronavirus disease 2019 (COVID-19) vaccination campaign underway, little is known about the vaccination coverage in patients with Parkinson’s disease (PD). OBJECTIVE: To investigate the vaccination status and reasons for COVID-19 vaccine acceptance and hesitancy among PD patients. METHODS: A survey was promoted to patients with PD via an online platform from April 2022 and May 2022. Logistic regression models were used to identify factors related to COVID-19 vaccine hesitancy.RESULTS: A total of 187 PD cases participated in this online survey. COVID-19 vaccination rate was 54.0%. Most patients had a fear of COVID-19 (77.5%) and trusted the efficacy (82.9%) and safety (66.8%) of COVID-19 vaccine. Trust in government (70.3%) and concerns about the impact of vaccine on their disease (67.4%) were the most common reasons for COVID-19 vaccine acceptance and hesitancy, respectively. COVID-19 vaccine hesitancy was independently associated with the history of flu vaccination (OR: 0.09, p < 0.05), trust in vaccine efficacy (OR: 0.15, p < 0.01), male gender (OR: 0.47, p < 0.05), disease duration of PD (OR: 1.08, p < 0.05) and geographic factor (living in Shanghai or not) (OR: 2.87, p < 0.01). CONCLUSIONS: The COVID-19 vaccination rate remained low in PD patients, however, most individuals understood benefits of vaccination. COVID-19 vaccine hesitancy was affected by multiple factors such as geographic factor, disease duration and trust in efficacy of vaccine. These findings could help government and public health authorities to overcome the barrier to COVID-19 vaccination and improve vaccine roll-out in PD patients.